I am proud working in McDonald’s: Are you a satisfied and loyal employee? - Herng, Law Lih; Balaraman, Lavhinesh A/L; Ceng, Lee Chiew; Lin, Lee Hui; Rahmasari, Erika Dwi Amelia; Ramadhani, Fadhila Puput; Srivastava, Shweta; Sharma, Juhi; Yusof, Rosmelisa (International Journal of Tourism and Hospitality in Asia Pasific, 2023)
One of the top fast-food restaurants in the world, McDonald's has more than 36,000 locations across the globe. In Malaysia, there are more than 320 branches country wide and they employ over 15000 employees around the country, supplying career, and development opportunities. This study aims to focus on how satisfied the employees are with their job and their loyalty towards the fast-food joint. Moreover, this study will also explain how the job satisfaction of the employees has a crucial part in shaping the employees' loyalty towards their workplace. For this study, we have surveyed the employees of five different McDonald’s branches in Malaysia and Indonesia, namely McDonald’s Kulim, McDonald’s Alma, McDonald’s E-Gate, McDonald’s Lowokwaru, and McDonald’s Darmo. Online surveys help to collect a huge amount of data while interviews provide deep and clear opinions and feelings of the employees. McDonald’s is familiar to many people. When McDonald’s understands and learns more about the employees’ satisfaction and loyalty, it is able to provide better service to the customers. As a customer, we can gain higher satisfaction.